Metadiscourse in academic writing of pre-university Arab students at the International Islamic University Malaysia (IIUM) - Zakaria, Muhamad Khairul; Abdul Malik, Faridah (EDP Sciences, 2018)
There is lack of studies on the use of metadiscourse markers; especially amongst international students studying in Malaysia and Malaysia are receiving scores of international students particularly from the Middle East annually. This study involves a textual analysis of students’ academic writing where the metadiscourse markers in 50 Arab IIUM students’ academic texts were identified and analyzed. The findings of this study indicated that Arab writers had a greater inclination for the deployment of the interactive markers (Total counts = 919) than interactional ones (Total counts = 592) as there was a higher percentage of interactive metadiscourse (60.8%) usage than the interactional ones (39.2%). It might be useful for English language teachers to integrate cultural considerations within their syllabus with regard to metadiscourse markers in order to prepare relevant materials based on their students’ needs as well as to develop the students’ awareness of the importance of these linguistic features.